2017
DOI: 10.3390/su9030430
|View full text |Cite
|
Sign up to set email alerts
|

Lime and Phosphate Amendment Can Significantly Reduce Uptake of Cd and Pb by Field-Grown Rice

Abstract: Agricultural soils are suffering from increasing heavy metal pollution, among which, paddy soil polluted by heavy metals is frequently reported and has elicited great public concern. In this study, we carried out field experiments on paddy soil around a Pb-Zn mine to study amelioration effects of four soil amendments on uptake of Cd and Pb by rice, and to make recommendations for paddy soil heavy metal remediation, particularly for combined pollution of Cd and Pb. The results showed that all the four treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…This decreases the activity of contaminants in soil that reduced phytotoxicity which ultimately leading to a significant increase in yield 46 . It has been reported that mixture of lime and phosphate amendments increased rice biomass in Cd contaminated field 47 . Liming was also testified to sustain crop yield in Cd contaminated soil 48 .…”
Section: Resultsmentioning
confidence: 98%
“…This decreases the activity of contaminants in soil that reduced phytotoxicity which ultimately leading to a significant increase in yield 46 . It has been reported that mixture of lime and phosphate amendments increased rice biomass in Cd contaminated field 47 . Liming was also testified to sustain crop yield in Cd contaminated soil 48 .…”
Section: Resultsmentioning
confidence: 98%
“…HAP is a typical inorganic chemical amendment that immobilized heavy metals 25 . Generally, the primary mechanisms of HAP for metal immobilization are adsorption, precipitation, cation exchange, and surface complexation, and involved processes as the follows [26][27][28] (Eqs. 2-4): HAP is dissolved in acidic soil, then Cd ions are adsorbed on the surface of HAP to form phosphate precipitates.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous reports on the application of lime for the remediation of heavy metal-contaminated soils have been published (Simón et al 2010;Hale et al 2012;Chen et al 2016;Cui et al 2016). In some previous studies, the application of lime significantly reduced Cd accumulation in rice grain below the Cd limiting standards (Bian et al 2016;Li et al 2016a;Xiao et al 2017). In these cases, lime was applied to heavy metal-contaminated paddy soils to immobilize Cd (Hu et al 2016).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%